The Synergistic Impact of Combined Massage and Stretching During Halftime on Accelerated Recovery in Football: A Quasi-Experimental Study on Lactic Acid Clearance, Pain Reduction, and Flexibility Improvement - Fatkur Rohman Kafrawi; Afif Rusdiawan; Ali Satia Graha; Nurhasan Nurhasan; Soni Sulistyarto; Cemal Özman; Achmad Widodo (Physical Education Theory and Methodology, 2025)
Background. Soccer players frequently encounter performance declines early in the second half due to diminished muscle temperature and the accumulation of fatigue indicators, such as lactic acid.